EFEKTIVITAS MEDIA PEMBELAJARAN ARTICULATE STORYLINE 3 DALAM PEMBELAJARAN TEKS PROSEDUR SISWA KELAS VII SMP N 8 PEKANBARU - Indah Rahayu Putri; Charlina; Silvia Permatasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the differences in learning outcomes between students who use the Articulate storyline 3 learning media and students who do not use the Articulate storyline 3 learning media in class VII students of SMP N 8 Pekanbaru and aims to determine the effectiveness of the use of the Articulate storyline 3 learning media on the learning of procedural texts of class VII students of SMP N 8 Pekanbaru. The research method in this study is an experiment through a quasi-experimental research type of pre-test and post-test with-non-equivalent control-group design. The sample of this study amounted to 72 students obtained by simple random sampling through drawing. The results of this study indicate that the learning outcomes of the trial class are superior compared to the control class. In the trial class, the average N-Gain score is 64.76, the interpretation of the effectiveness category of the N-Gain experimental class is quite effective and the N-Gain control class is 48.13, the interpretation of the effectiveness category of the N-Gain control class is less effective. The results of the N-Gain test can prove that in learning procedural texts the use of the Articulate storyline 3 learning media is effectively applied in learning.